The Effect of Drug Planning, Internal Control, and Payment Accuracy on Drug Inventory in Health Facilities - Senima Kurniawati; Rosidi; Umi Muawanah (Journal of Educational Management Research, 2026)
This study aims to examine the influence of drug planning, internal control, and payment accuracy on drug inventory management within healthcare facilities from an educational management perspective. Specifically, it integrates management dimensions such as planning, organizing, controlling, and financial accountability in institutional governance. A quantitative approach was employed using a census method with 70 respondents directly involved in drug inventory management. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that drug planning has a significant positive effect on drug inventory (t = 2.304, p = 0.024), internal control shows no significant effect (t = 0.446, p = 0.657), and payment accuracy has a significant positive effect with the strongest influence (t = 2.814, p = 0.006, β = 0.370). Simultaneously, all variables significantly affect drug inventory management (F = 13.297, p = 0.000). These findings imply the need to strengthen data-driven planning systems, enhance managerial control mechanisms aligned with institutional capacity, and prioritize financial accuracy to ensure sustainable drug availability and service continuity.